Patriotism and its Importance in Attracting Young People to the Armed Forces - Mamadalimov Azimjon Xasanboevich (Genius Journals, 2023)
This in the article makes the youth of the armed forces attractive to the system. The mud of Ministry in the system studies the formation and development of a sense of zeal and patriotism about this statement.
Keywords: Motherland; patriotism; protection; service